Synthesis, complexation and electrochemistry of novel ferrocenyl chalcogenide ligands. - Su Jing (2006)
The aim of this work was the synthesis of novel ferrocenyl chalcogenide ligands and their late transition metal complexes, and the study of relevant electrochemistry to provide information for exploring their potential application in a new type of electrochemical sensor. The introduction reviews four sections of the literature. Group 6 metal carbonyl and palladium, platinum complexes of neutral chalcogenoether ligands are briefly introduced. The electrochemistry of linked ferrocenes is explored. Finally, the use of ferrocene in the design of electrochemical sensors is described. Subsequent chapters describe the synthesis and characterisation of novel ferrocenyl chalcogenide compounds, which can be divided into three categories: (1) Four series of ferrocenyl chalcogenide compounds with flexible saturated hydrocarbon chains: bidentate, linear tridentate, tripodal or tetradentate ligands; (2) Two macrocyclic ferrocenyl selenide compounds with four Se donor atoms; (3) Three ferrocenyl chalcogenide compounds with a rigid chain. Four compounds' structures have been determined by X-ray crystallography: FcSe(CH2)3SeFc, FcSe(CH2)3Se(CH2)3SeFc, difcSe4 and FcSeCH2C6H4CH2SeFc. The coordination chemistry of ferrocenyl chalcogenide compounds was then systematically studied. New compounds include: (1) Palladium and platinum complexes of the ligands with flexible saturated hydrocarbon chains; (2) Group 6 metal carbonyl complexes of bis(ferrocenylchalcogeno)propanes; (3) Palladium and platinum complexes of the macrocyclic ligands; (4) The platinum complex of FcSeCH2C6H4CH2SeFc. Techniques used to characterize these compounds include: multinuclear NMR spectroscopy; mass spectrometry; UV-vis and IR spectroscopy. Eighteen complexes' structures have been determined by X-ray crystallography: [MlcubFcE(CH2)3E'Fc{rcub}2](PF6)2 (M = Pd or Pt; E, E' = Se or Te), [MCl2(FcSeCH2SeFc)2] (M = Pd or Pt), [MCl2(FcTeCH2TeFc)] (M = Pd or Pt), [PdCl2(FcSeCH2CH2SeFc){rcub}, [PtCl lcubFcSe(CH2)3Se(CH2)3SeFcrcub ]PF6, [Cr(CO)4lcubFcTe(CH2)3TeFcrcub], [Mo(CO)4lcubFcE(CH2)3E'Fcrcub] (E, E' = Se or Te), [W(CO)4lcubFcTe(CH2)3TeFcrcub], and the supramolecular complex [Pt2Cl2lcubFcSeCH2C6H4CH2SeFc{rcub}3l(PF6)2 with an unusual dinuclear triple helical geometry. The electrochemistry study of the above compounds by cyclic voltammetry and differential pulse voltammetry proved that the communication between ferrocene units occurs via a through bond mechanism, and it is tentatively concluded that the interaction between ferrocene units can only happen when they occupy inequivalent positions.